Foreign tourists’ preference for translation strategy applied to translate Vietnamese dishes = Quan điểm của du khách nước ngoài về chiến lược dịch tên món ăn Việt Nam - Đào, Khánh Huyền (2021)
Being cited among the world’s best street food destinations by the eminent magazine Food & Wine and the acclaimed travel website CNNGo, Vietnam has gained increasing prestige for its diverse and unique cuisine. However, fame does bring about challenges that need to be confronted in the pursuit of promoting Vietnam in the international community. Among those challenges, the most daunting one may be the issue of how to introduce Vietnamese culture in general and Vietnamese cuisine in particular by means of language. Translating culture-specific items, particularly dishes’ names which are embedded with both communicative and cultural connotations, has never been an easy task. Therefore, this research was conducted to reach out for foreign tourists’ opinions on translation of Vietnamese dishes with the hope to assist translators and translator-to-be in producing the most satisfying translation. The research was conducted on 80 randomly-picked foreign tourists in the Old Quarter, Hanoi to gather their opinions and preference on the translation strategy that should be applied to translate Vietnamese dishes in general and a list of 10 representative dishes in particular. Questionnaire is used as the major research tool, followed by follow-up interviews delivered to a certain group of respondents. Data was collected and analyzed using several sets of tools and index. As the result showed, tourists’ preference for translation strategy are influenced by six major factors. A number of impacts that each translation strategy has on foreign tourists were also discovered and reasoned.